Combinação de treino aeróbico e de força em pacientes com insuficiência cardíaca: meta-análise e meta-regressão - Righi, Geovana de Almeida (2019)
Patients with heart failure (HF) tend to present dyspnea, fatigue and decreased exercise intolerance, changes that affect quality of life. Isolated aerobic training (AT) in combination with strength training has been shown to be beneficial for VO2 peak and muscle strength when compared to a control group. When comparing the combined training (CT), defined by the association of strength training with AT, gold standard for non-pharmacological treatment of this population, the results are controversial and more elucidations are necessary due to limitations present in previous reviews such as inadequate classification of studies, non-exploration of heterogeneity, low sensitivity of research, some reviews with low number of included articles and etc. The objective of the study was to systematically review the effects of CT versus AT or control on functional capacity, by the measurement of VO2 peak, and quadriceps muscle strength. The databases Pubmed/MEDLINE, EMBASE, Cochrane CENTRAL, PEDro, SPORTDiscus and Lilacs were used. Randomized clinical trials with subjects with HF were included, who compared the effects of CT versus AT or control on VO2 peak and quadriceps muscle strength. We included 28 articles, divided into four analyzes. The CT increased VO2 peak and quadriceps muscle strength compared to the control. CT was similar to TA in improving VO2 peak but with better effects on quadriceps strength. There were no differences between AT modalities. Low number of studies included, lack of consensus and detailed description of rehabilitation protocols made it more difficult to speculate on subgroup and meta-regression analyzes. CT improves functional capacity and muscle strength, but does not differ from AT for improvement in VO2 peak. Strength training should be encouraged in cardiac rehabilitation programs, but when infeasible, AT can be performed in isolation to increase functional capacity.